Integrating campus image and users' sense of place in the University of the Philippines Mindanao campus development - Espirituoso, Reyl B.
The physical campus denotes the idea of 'going to the university and with the popularization of online learning, the role of campuses as an important part of a pedagogical environment is changing and diminishing. In terms of higher education learning. Dr Toope (2014) suggests that two factors must be met for students to continue to go to universities; one, superior reputation or brand, and two, rich and unique on-campus experience How can the campus-built environment affect the on-campus experience and how can it be manipulated' How can designers be able to strengthen the campus image and how can they enrich this on-campus experience' The researcher was able to determine that sense of place using Bott's Model of Sense of Place can be used as a measure of the on-campus experience and that campus image can be operationalized by utilizing the Identity gradient of Rugerri (2013). University of the Philippines Mindanao as the chosen case study and its user-defined campus with seven locations, has a current campus image influenced by accessibility and local culture. On the other hand, the current sense of place of the campus is strongly influenced by the natural environment, integration, and user satisfaction. The UP Mindanao Campus sense of place study was able to support the notion that sense of place has an organic development and it exist in itself by itself. The proposed UP Mindanao Research Block Development would exhibit the resulting design principles of the research and will illustrate the ability to of the established pre-design process of the research to update the UP Master Development Plan.